Deep-Tissue Reporter-Gene Imaging with Fluorescence and Optoacoustic Tomography: A Performance Overview - Deliolanis, Nikolaos C.; Ale, Angelique; Morscher, Stefan; Burton, Neal C.; Schaefer, Karin; Radrich, Karin; Razansky, Daniel; Ntziachristos, Vasilis (Molecular Imaging and Biology, 2014)
Purpose: A primary enabling feature of near-infrared fluorescent proteins (FPs) and fluorescent probes is the ability to visualize deeper in tissues than in the visible. The purpose of this work is to find which is the optimal visualization method that can exploit the advantages of this novel class of FPs in full-scale pre-clinical molecular imaging studies.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Fluorescent proteins; Glioma; Optical imaging; Optoacoustic (photoacoustic) tomography; Reporter genes